KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP KELAS VIII PADA MATERI KOORDINAT KARTESIUS DENGAN PENDEKATAN SAINTIFIK - Gita Sintia; M. Afrilianto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to examine the mathematical problem solving abilities of junior high school students at MTs An-Nur class VIII on Cartesian Coordinates using a scientific approach. This research is a Classroom Action Research (CAR). The research subjects are junior high school students at MTs An-Nur class VIII with a total of 22 students. The research instruments used in this study were pretest and posttest questions on mathematical problem-solving abilities, observation sheets for teacher and student activities, and student learning independence questionnaires. This classroom action research was carried out in 2 cycles, with the stages of the research, namely: planning, action, observation and reflection. The results showed that there was a mathematical problem solving ability of junior high school students using a scientific approach.